Analisis Studi Kelayakan Usaha Pada Gans Kedai Tembakau di Kota Serang, Banten - Ahyakudin; Elif Pardiansyah; Mohamad Ainun Najib (STEKOM PRESS, 2023)
This research is motivated by the role of tobacco which is one of the important agribusinesses in Indonesia and has contributed to the national, regional and community economies. Seeing this opportunity, conducting a business feasibility study is necessary to improve the Indonesian tobacco industry. This type of research is a field study. The method used is descriptive qualitative method. This research was conducted in Sumurpecung Village, Serang District, Serang Banten Regency. Data analysis techniques in this study include descriptive descriptions to analyze the financial and non-financial aspects. The results of this study indicate that the overall business feasibility in terms of non-financial aspects consisting of legal, marketing, technical, management, social-economic, and environmental impact aspects are declared feasible to run. Likewise, the financial aspect as a whole was declared feasible to run. Based on this, it can be concluded that the tobacco business run by Gans tobacco shop in Serang City is feasible to run based on an assessment of financial and non-financial aspects.